Langerhans Cells: Sensing the Environment in Health and Disease - Deckers, Julie; Hammad, Hamida; Hoste, Esther (Frontiers in Immunology, 2018)
In the last decades our understanding of Langerhans cells (LCs) has drastically changed based on novel findings regarding the developmental origin and biological functions of these epidermis-specific resident immune cells. It has become clear that LCs exert pivotal roles in immune surveillance and homeostasis, but also impact on pathology by either inducing tolerance or mediating inflammation. Their unique capabilities to self-renew within the epidermis, while also being able to migrate to lymph nodes in order to present antigen, place LCs in a key position to sample the local environment and decide on the appropriate cutaneous immune response. Exciting new data distinguishing LCs from Langerin+ dermal DCs on a functional and ontogenic level, reveal crucial roles for LCs in trauma and various skin pathologies, which will be thoroughly discussed here. However, despite rapid progress in the field, the exact role of LCs during immune responses has not been completely elucidated. This review will focus on what mouse models that have been developed in order to enable the study of murine LCs and other Langerin-expressing dendritic cells, have taught us about LC development and function.